Perilaku Masyarakat yang Berdampak Terhadap Pencemaran Sungai di Kelurahan Kuin Utara Kota Banjarmasin - Nikmah, Rizkiatun; Budhi, Setia (Prodi Sosiologi FISIP ULM, 2024)
Pollution of the Kuin River has caused a decline in river water quality. This research aims to find out the behaviour of the community that causes pollution of the Kuin River, as well as to find out the efforts made in improving the river. The analysis of this research uses the theory of risk society and the theory of environmental ethics. This research uses a qualitative method. Data collection used observation, interview and documentation techniques. The research was conducted for 2 months, from December 2022 - January 2023. The research was conducted in North Kuin Village, North Banjarmasin District, Banjarmasin City. Data analysis techniques consist of data reduction, data presentation and conclusion drawing. The results show that the behaviour of the people of Kuin Utara Village in relation to the river is very diverse. These behaviours have become habits that are difficult to change. People understand that throwing rubbish into the river is a bad habit. The lack of cleaning facilities is also a reason for people to litter. In addition, the lack of government role is one of the factors, where the government's role in handling waste is still very limited compared to the level of waste volume generated every day. Community efforts in improving the river environment are carried out through tree planting activities. Mutual cooperation activities to clean up rubbish are also carried out to create a healthy and clean river environment. These efforts also contribute to the preservation of cultural and religious heritage tourism in Kuin Utara Village. If people do not have a healthy lifestyle, the environment will be polluted, so the role of the entire community is needed to create a clean and comfortable environment.